A CONCEPTUAL OVERVIEW OF EMPATHY IN THE CONTEXT OF HUMANISTIC PSYCHOLOGY - Tatlılıoğlu, Kasım (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
One of the important concepts of humanistic psychology is empathy. Humanistic psychology by the process of realizing and expressing one’s own capabilities. There is little consensus about what empathy. Empathy is the process of experiencing the emotions and cognitions of another person and transmitting this situation to him/her. Most broadly, empathy involves the capacity to share the mental lives of others. Empathy is crucial for interpersonal communication.Debates about empathy’s is complex. In this article is discussed the concept of empathy one of the important concepts of humanistic psychology.